2017
DOI: 10.1186/s12879-017-2634-z
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of Plasmodium falciparum k13-propeller gene among migrant workers returning to Henan Province, China from Africa

Abstract: BackgroundHenan Province has been in the malaria elimination stage, with all reports of the disease being imported since 2012 and over 90% coming from Africa. Surveillance and population studies are essential for the early detection and subsequent prevention of the spread of drug resistance. The K13-propeller gene was recently identified as a proposed molecular marker of artemisinin (ART) resistance. In this study, we detected mutations of the K13-propeller gene in samples taken from imported malaria cases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 25 publications
5
38
1
Order By: Relevance
“…But, the exact place of the infection can not be confirmed now, because we lost contact with the patient in 2013. samples returned to China from Africa. 11,20 Our data indicate that the most prevalent African mutation was A578S, whereas other mutations had low prevalence. This puts our findings in line with those reported by Ménard et al, 17 whereby many K13-propeller mutations appeared to be neutral and failed to undergo clonal expansion in Africa.…”
Section: Discussionmentioning
confidence: 65%
“…But, the exact place of the infection can not be confirmed now, because we lost contact with the patient in 2013. samples returned to China from Africa. 11,20 Our data indicate that the most prevalent African mutation was A578S, whereas other mutations had low prevalence. This puts our findings in line with those reported by Ménard et al, 17 whereby many K13-propeller mutations appeared to be neutral and failed to undergo clonal expansion in Africa.…”
Section: Discussionmentioning
confidence: 65%
“…The mutations of Pfk13-propeller are well established in Southeast Asia, whereas only limited polymorphisms of Pfk13-propeller are detected in Africa [16,46]. Recently, in China, polymorphism in Pfk13 was reported in returned migrant workers from Africa [47]. Thus, there is now a clear need to acquire a greater understanding of Plasmodium parasites' genotypic resistance surveillance with k13-propeller polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Africa [20]. The only previous data on PfKelch13 polymorphism performed in 2014 in the CAR (K13 artemisinin resistance multicenter resistance, KARMA study), revealed a 4.5% prevalence of nonsynonymous mutations [12].…”
Section: Resultsmentioning
confidence: 96%
“…Guinea and in Rwanda, whereas mutations potentially associated with artemisinin resistance (M476I) have been detected in Senegal [20,21,22,23]. A particular case was the observation of a local mutation (M579I) in Equatorial Guinea [24].…”
Section: Resultsmentioning
confidence: 99%